Problems of Islamic Religious Education Teachers In Implementing the Independent Curriculum - Shinta Sri Pillawaty (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
Islamic Religious Education (PAI) teachers have a crucial role in creating a superior generation both in terms of domination of science and technology (IPTEK) and in strengthening faith and piety (IMTAQ). with the Law that education aims to produce generations who are faithful, pious, have noble character, are intelligent, independent, creative, and responsible. The existence of the Independent Curriculum which is implemented at SMA Yadika Kalijati Subang in class X at this time, is becoming a problem, especially for PAI teachers in implementing the Independent Curriculum at school. The purpose of this research is to describe how the independent curriculum is implemented by PAI teachers and to describe the problems of PAI teachers in implementing the independent curriculum. This research method uses qualitative interviews and document studies. The results of this study can be interpreted that PAI teachers in implementing the independent curriculum tend to be difficult to implement because the independence of students still needs special attention. So this is a problem faced by PAI teachers in implementing the independent learning curriculum, besides being required to be a facilitator the teacher must also be able to form active and creative students, this is difficult to implement if students tend to only follow directions from the teacher without any initiative of their own.Keywords: Education, Islamic, Curriculum, PAI